1993
DOI: 10.1007/bf02602962
|View full text |Cite
|
Sign up to set email alerts
|

Lipiodol retention and massive necrosis after lipiodol-chemoembolization of hepatocellular carcinoma: Correlation between computed tomography and histopathology

Abstract: This retrospective study examined the computed tomography (CT) criteria for judging the effectiveness of transcatheter arterial Lipiodol-chemoembolization (Lp-chemo-TAE) in 35 cases with hepatocellular carcinoma (HCC). Massive necrosis, defined as involving 97% or more of the HCC nodule, was observed in 15 cases after Lp-chemo-TAE, whereas nonmassive necrosis, defined as involving < or = 96% of the HCC nodule, was observed in the remaining 20 cases. In 12 of 15 cases (80%) with massive necrosis, uniform dense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 11 publications
1
38
1
Order By: Relevance
“…Therefore different imaging modalities for evaluation of TACE efficacy have been described. Many studies [9][10][11][12] have shown that the TACE effectiveness can be judged based on the degree of iodized oil retention, as a close correlation between accumulation of iodized oil emulsion and tumor necrosis has been demonstrated histologically [13,14]. A complete retention of iodized oil emulsion on CT images was correlated with a 98% necrosis of resected specimen [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore different imaging modalities for evaluation of TACE efficacy have been described. Many studies [9][10][11][12] have shown that the TACE effectiveness can be judged based on the degree of iodized oil retention, as a close correlation between accumulation of iodized oil emulsion and tumor necrosis has been demonstrated histologically [13,14]. A complete retention of iodized oil emulsion on CT images was correlated with a 98% necrosis of resected specimen [11].…”
Section: Discussionmentioning
confidence: 99%
“…A complete retention of iodized oil emulsion on CT images was correlated with a 98% necrosis of resected specimen [11]. Imaeda et al [9] evaluated the effectiveness of TACE based on the measurements of attenuation values of the nodules after TACE. These authors concluded that a cutoff value of 365 HU corresponded to massive necrosis (>97% of the nodule) with 89% sensitivity and 73% specificity.…”
Section: Discussionmentioning
confidence: 99%
“…We regarded lipiodol accumulation in targeted tumors seen on CT scans as indicating necrosis. This was due to the fact that it had been previously reported in several studies that the lipiodol retention areas observed on CT corresponded to necrotic areas (25)(26)(27). Complete response (CR) was defined as the disappearance of all targeted tumors or 100% tumor necrosis, partial response (PR) was defined as a ≥50% reduc-tion in tumor size and/or necrosis, and progressive disease (PD) was defined as >25% tumor enlargement and/or the appearance of any new HCC tumors.…”
Section: Methodsmentioning
confidence: 91%
“…We regarded LPD accumulation in the tumor as representing a necrotic area, based on previous reports of such LPD retention areas corresponding to the necrotic areas on CT. [20][21][22][23] By measurement of the two largest perpendicular diameters of the tumor, we classified tumor response into four categories using the following criteria: complete response (CR), complete disappearance or 100% necrosis of all tumors; partial response (PR), reduction and/or necrosis, with a decrease of at least 50% in all measurable lesions; progressive disease (PD), an increase in tumor size exceeding 25% of all measurable lesions or appearance of a new lesion; stable disease (SD), disease not qualifying for classification as CR, PR, or PD.…”
Section: Post-treatment Assessmentmentioning
confidence: 99%